A high‐order curvature‐corrected CMOS bandgap voltage reference with constant current technique. (1st August 2012) - Geng, Junfeng; Zhao, Yiqiang; Zhao, Hongliang
SUMMARY A high‐order curvature‐corrected complementary metal–oxide–semiconductor (CMOS) bandgap voltage reference (BGR), utilizing the temperature‐dependent resistor and constant current technique, is presented. Considering the process variation, a resistor trimming network is introduced in this work. The circuit is implemented in a standard 0.35‐µm CMOS process. The measurement results have confirmed that the proposed BGR operates with a supply voltage of 1.8 V, consuming 45 μW at room temperature (25 °C), and the temperature coefficient of the output voltage reference is about 5.5 ppm/°C from −40 °C to 125 °C. The measured power supply rejection ratio is −38.8 dB at 1 kHz. The BGR is compatible with low‐voltage and low‐power circuit design when the structure of operational amplifiers and all the devices in the proposed bandgap reference are properly designed. Copyright © 2012 John Wiley & Sons, Ltd.